RNAi in the model system Drosophila - Carthew, Richard (Henry Stewart Talks, 2007)
Understanding how RNAi works, The fruitfly, Drosophila melanogaster model, The three reasons for the success of the model, RNAi mechanism in Drosophila and humans is similar, Rich history of genetics in Drosophila, Robust chemistry of the Drosophila system, Fusion of genetics and biochemistry, Discovery of RISC, Discovery of Dicer, Discovery of Ago2, New features of RNAi biochemistry, Greater understanding of how double-helix RNA is used to silence genes, Development of RNAi for disease research and treatment
Archived at 2017/09/28